Effects of Absorber Emissivity on Thermal Performance of a Solar Cavity Receiver - Jiabin Fang; Nan Tu; Jinjia Wei (Advances in Condensed Matter Physics)
Solar cavity receiver is a key component to realize the light-heat conversion in tower-type solar power system. It usually has an aperture for concentrated sunlight coming in, and the heat loss is unavoidable because of this aperture. Generally, in order to improve the thermal efficiency, a layer of coating having high absorptivity for sunlight would be covered on the surface of the absorber tubes inside the cavity receiver. As a result, it is necessary to investigate the effects of the emissivity of absorber tubes on the thermal performance of the receiver. In the present work, the thermal performances of the receiver with different absorber emissivity were numerically simulated. The results showed that the thermal efficiency increases and the total heat loss decreases with increasing emissivity of absorber tubes. However, the thermal efficiency increases by only 1.6% when the emissivity of tubes varies from 0.2 to 0.8. Therefore, the change of absorber emissivity has slight effect on the thermal performance of the receiver. The reason for variation tendency of performance curves was also carefully analyzed. It was found that the temperature reduction of the cavity walls causes the decrease of the radiative heat loss and the convective heat loss.